DisPossession : haunting in Canadian fiction - Goldman, Marlene, 1963- (McGill-Queen's University Press, 2012)
"Much of Canada's contemporary fiction displays an eerie fascination with the supernatural. In DisPossession, Marlene Goldman investigates the links between spectral motifs and the social and historical influences that have shaped Canada.